MEDICINE HERBS (TOBA) PARK PLANNING IN STRUCTURING PUBLIC HEALHT CENTER (PUSKESMAS) - Gunarto, Anton (BPPT)
Medicine Park Herbalia or Toba Puskesmas (Public Health Center) designed in their yards with the goal as a liaison between the human and the natural environment created to meet the spiritual needs (a beautiful atmosphere, secure, peaceful, relaxed, passive recreation, as a means of social and education) and physical needs (as ingredients, versatile, active recreation) for the occupants of Public Health Center or the owner of Toba. Toba can be said to succeed if the owner liked toba extent of the function and aesthetic value in accordance with the principles of design (theme, gradation, contrast, control) which is expressed in design elements (size, shape, texture, color). For simplicity in selecting the elements forming the park and in maintaining the design Toba need appreciation of art and science and technology through the introduction of the factors softscape and hardscape.keywords : medicine herbs park, public healht center (puskesmas)